Adaptasi tes inteligensi CFIT skala 2 bagi siswa tunanetra di SLB/A DIY dan Jawa Tengah = The Adaptation of Intelligence Test CFIT Scale 2 for Blind Students in SLBIA of DIY and Central Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
The adaptation of test CFIT Scale 2 is an attempt to develop intelligence test which is expected to be useful for students in SLB/A (special school for visual handicapped) in general. The adaptation was done by modifying the test size, materials, and tehnique to do the test, and the time to administer the test. The size of the test stimuli were enlarged. The picture was printed protrusively. The test materials used were Braillon papers. The answer sheet used Braille letters and the time allocated to do the test was prolonged three times longer than the time allocated to the original test. Subjects of this research were pupils in SLB/A (special school for visual handicapped) in the provincies of Yogyakarta Special Territory and Central Java. Subjects in the try-out stage were 44 and students, in the study stage were 130 students from 3 SLB/A's. They were chosen randomly and the number of subjects were gained from all number of SLB /A students who fulfilled the research requirements. The age of subjects ranged from 9 to 19 years. They consisted of the D3 until L3 levels. Tehnique of Product-Moment Correlation was used to test the item and subtes internal validity. Alpha Coefficient for reliability, and Varimax Rotation for Factor Analysis were also used. Result showed that the adapted Test CFIT Scale 2 for the blind students has internal validity. It was also revealed that there has only one factor of the Adaptation Test of CFIT Scale 2. This showed that the adaptation Test CFIT Scale 2 had fulfilled the requirements to be a valid and reliable psychological test.